Pengaruh kecepatan weaving terhadap keseragaman dan Lebar Manik Las dengan Ketinggian Torch 2 mm Pada Pengelasan Orbital pipe welding (OPW) SS316L - Prasetyo, Eko; Baskoro, Ario Sunar; Silalahi, Yabes Gomest; Fikri, Muhammad; Kiswanto, Gandjar (Prosiding SNTTM, 2024)
Pipe welding is widely used in industries with piping systems, including the oil, construction, and manufacturing industries. Several parameters, including the width of the weld bead, can determine the quality of good welding results. In this research, pipe welding was carried out automatically in the 5G position using GTAW (Gas Tungsten Arc Welding) without metal filler (Autogenous). Welding tests were carried out to determine the effect of weaving speed on the uniformity of weld bead width from 0° to 360° and the weld bead width of 316L Stainless Steel pipes with an inner diameter of 4 inches and a thickness of 4 mm using a zigzag (weaving) welding pattern. The welding method uses the Pulse Current Gas Arc Welding (PC-GTAW) method with a current of 137 A and a background current of 10 PPS (Pulse Per Current). Test samples were taken at 4 (four) welding points, namely 0°, 90°, 180° and 270° with a torch height of 2 mm to the test object. The test was carried out with 3 (three) variations of weaving speed, namely 0.150 mm/s, 0.155 mm/s, and 0.161 mm/s. The welding tool used is a prototype orbital pipe welding tool using the 5G method, which is then carried out by forming a test object. Weld bead width was measured using a digital microscope model Dino-Lite AM 4515ZT and DinoCapture 3.0 software. The bead width measurements show that the most consistent weld bead width uniformity occurs at a weaving speed of 0.155 mm/s. Meanwhile, the average weld bead width at a weaving speed of 0.150 is 10.26 mm; at a weaving speed of 0.155 mm/s, it is 10.44 mm; and at a weaving speed of 0.161 mm/s, the average weld bead width is 9.8 mm.